Hypoxia Induces Renal Epithelial Injury and Activates Fibrotic Signaling Through Up-Regulation of Arginase-II - Liang, Xiujie; Potenza, Duilio Michele; Brenna, Andrea; Ma, Yiqiong; Ren, Zhilong; Cheng, Xin; Ming, Xiu-Fen; Yang, Zhihong (Frontiers in Physiology, 2021)
The ureohydrolase, type-II arginase (Arg-II), is a mitochondrial enzyme metabolizing L-arginine into urea and L-ornithine and is highly expressed in renal proximal tubular cells (PTC) and upregulated by renal ischemia. Recent studies reported contradictory results on the role of Arg-II in renal injury. The aim of our study is to investigate the function of Arg-II in renal epithelial cell damage under hypoxic conditions. Human renal epithelial cell line HK2 was cultured under hypoxic conditions for 12 to 48 hours. Moreover, ex vivo experiments with isolated kidneys from wild-type (WT) and genetic Arg-II deficient mice (Arg-II-/-) were conducted under normoxic and hypoxic conditions. The results show that hypoxia upregulates Arg-II expression in HK2 cells, which is inhibited by silencing both hypoxia-inducible factors HIF1α and HIF2α. Treatment of the cells with dimethyloxaloylglycine (DMOG) to stabilize HIFα also enhances Arg-II. Interestingly, hypoxia or DMOG upregulates transforming growth factor β1 (TGFβ1) levels and collagens Iα1, which is prevented by Arg-II silencing, while TGFβ1-induced collagen Iα1 expression is not affected by Arg-II silencing. Inhibition of mitochondrial complex-I by rotenone abolishes hypoxia-induced reactive oxygen species (mtROS) and TGFβ1 elevation in the cells. Ex vivo experiments show elevated Arg-II and TGFβ1 expression and the injury marker NGAL in the WT mouse kidneys under hypoxic conditions, which is prevented in the Arg-II-/- mice. Taking together, the results demonstrate that hypoxia activates renal epithelial HIFs-Arg-II-mtROS-TGFβ1-cascade, participating in hypoxia-associated renal injury and fibrosis.